2007
DOI: 10.1111/j.1524-475x.2007.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and guidance of cell behavior for tissue regeneration via the siRNA mechanism

Abstract: RNA intereference and short-interfering RNA (siRNA) have been proven to be effective at decreasing the expression of target genes and provide a valuable tool for promoting and directing the growth of functional tissues for repair and reconstructive tissue engineering applications. siRNA is a gene-silencing mechanism that involves double-stranded RNA-mediated sequence-specific mRNA degradation and is a powerful mechanism for controlling cell behavior. The use of siRNA to reduce the expression of a target gene c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 59 publications
0
36
0
Order By: Relevance
“…These genes encode for secreted proteins that work synergistically to recruit and support cells that are directly involved in angiogenesis and result in wound healing and repair. 23,[26][27][28][29] The implantation of human progenitor cells induces the migration and resultant angiogenesis from responsive rodent endothelial cells, 30,31 and we detected increased vascularization in defect sites treated with human MSCs in the presence and absence of ECFCs. These data provide evidence that the observed increases in cellular survival or proliferation are due in part to growth factor production, with more than twice the VEGFA, FGF1, and PDGF expression by MSCs on HA-containing scaffolds.…”
Section: Discussionmentioning
confidence: 65%
“…These genes encode for secreted proteins that work synergistically to recruit and support cells that are directly involved in angiogenesis and result in wound healing and repair. 23,[26][27][28][29] The implantation of human progenitor cells induces the migration and resultant angiogenesis from responsive rodent endothelial cells, 30,31 and we detected increased vascularization in defect sites treated with human MSCs in the presence and absence of ECFCs. These data provide evidence that the observed increases in cellular survival or proliferation are due in part to growth factor production, with more than twice the VEGFA, FGF1, and PDGF expression by MSCs on HA-containing scaffolds.…”
Section: Discussionmentioning
confidence: 65%
“…Tissue engineering deals with the reconstruction of degenerative tissues using three-dimensional cell-laden scaffolds, where morphogenesis is precisely induced and cell-matrix interaction is highly emphasized [41,42]. Gradual release of naked or formulated (i.e.…”
Section: Macroscopic Matrix Systemsmentioning
confidence: 99%
“…hydrid systems) siRNA from macroscopic matrices causing a continuous downregulation of undesired regulatory proteins or enzymes at the post-transcriptional level is indeed a promising application for siRNA. The potential of siRNA in regenerative medicine has already been illustrated by various applications for angiogenesis, wound healing and bone or nerve regeneration [41] but up to date, the use of matrix systems for these applications is still unexploited.…”
Section: Macroscopic Matrix Systemsmentioning
confidence: 99%
“…Gene therapy offers a promising approach for promoting lineage-specific differentiation by up-regulating inductive genes via DNA delivery and/or down-regulating inhibitory genes via RNA interference delivery (9,10). Previous reports have shown that BMP-transduced ADSCs using adenovirus led to overexpression of BMP2 and enhanced bone formation in vivo (3).…”
Section: Introductionmentioning
confidence: 98%
“…These results suggest that co-delivery of multiple signals may act synergistically to accelerate stem cell differentiation. While extensive work has been performed on delivery of inductive genes for promoting stem cell differentiation, efforts on employing inhibitory gene delivery to enhance stem-cell differentiation are only beginning to emerge (10). RNA interference is a gene-silencing mechanism that involves double-stranded RNA-mediated sequence-specific mRNA degradation and is a powerful mechanism for controlling cell behavior.…”
Section: Introductionmentioning
confidence: 99%